Calibrated versus uncalibrated arterial pressure waveform analysis in monitoring cardiac output with transpulmonary thermodilution in patients with severe sepsis and septic shock: An observational study. Issue 1 (January 2015) - Slagt, Cornelis; Helmi, Mochamat; Malagon, Ignacio; Groeneveld, A.B. Johan
Abstract : BACKGROUND: Cardiac output ( CO ) measurement is often required in critically ill patients. The performances of newer, less invasive techniques require evaluation in patients with severe sepsis and septic shock. OBJECTIVES: To compare calibrated arterial pressure waveform analysis-derived CO (COap, VolumeView/EV1000) and the uncalibrated form (COfv, FloTrac/Vigileo) with transpulmonary thermodilution derived CO (COtptd). DESIGN: A prospective, observational, single-centre study. SETTING: ICU of a general teaching hospital. PATIENTS: Twenty consecutive patients with severe sepsis or septic shock requiring haemodynamic monitoring by VolumeView/EV1000 and receiving mechanical ventilation. INTERVENTION: Connection of FloTrac/Vigileo to radial artery catheter already in situ . MAIN OUTCOME MEASURES: Radial (COfv) and femoral (COap) arterial waveform-derived CO measurements were compared with COtptd with respect to bias, precision, limits of agreement and percentage error, and the percentage error in the course of time since the last calibration of COap by COtptd. RESULTS: In comparing COap with COtptd ( n  = 267 paired measurements), the bias was 0.02 and limits of agreement were −2.49 to 2.52 l min −1, with a percentage error of 31%. The percentage error between COap and COtptd remained less than 30% until 8 h after calibration. In comparing COfv with COtptd ( n  = 301), the bias was −0.86 l min −1 and limits of agreement were −4.48 to 2.77 l min −1, with a percentage error of 48%. The biases of COap and COfv correlated with systemic vascular resistance [ r  = 0.13 ( P  = 0.029) and r  = 0.42 ( P  < 0.001), respectively]. Clinically significant changes in COap and COfv correlated positively with COtptd at r  = 0.51 ( P  < 0.001) and r  = 0.64 ( P  < 0.001), respectively. CONCLUSION: There was moderate agreement when measuring CO with either arterial waveform analysis technique. Compared with the uncalibrated COfv, the recently introduced calibrated arterial pressure waveform analysis-derived COap was more accurate and less dependent on vascular tone for up to 8 hours after callibation when monitoring CO in patients with severe sepsis and septic shock. The COap and COfv methods have poor to moderate CO -tracking abilities. This article is accompanied by the following Invited Commentary: Crossingham I, Columb M. Moderate agreement for cardiac output monitors. Moderately good or moderately bad? Eur J Anaesthesiol 2015;32 :1–2.